HUBUNGAN DEPRESI DENGAN INTERAKSI SOSIAL LANJUT USIA DI DESA TOMBASIAN ATAS KECAMATAN KAWANGKOAN BARAT - Rau, Nia Aprindah; Rompas, Sefti; Kallo, Vandri D (Universitas Sam Ratulangi, 2017)
Abstract : The process of aging was a lifelong process that was not only starting from a certain time,but starting from the beginning of life. An increasing number of elderly followed by health problemsfaced due to the degenerative process. Due to the physical and psychological changes of theelderly,many of them were depressed which is one of the most mental illnesses that occur in the world.Social interaction wasinterplayamong individual relationshipswith one another with the resultthatinfluenced, alter, or improve the behavior of other individuals or vice versa. The purpose of thisresearch wasto knowing the Correlation between Depression with Social Interactions of the Elderlyat the village of Upper Tombasian, District of West Kawangkoan. The Design of This Study usedcross sectionalthat is the data which related to the independent variables and the dependent variableor risk or due to be collected in the same time. The sample was taking by using the purposive samplingtechnique with a total sample of 61 respondents. The results of the statistical testof Chi-Square witha confidence level of 95% (Î± = 0.05) and obtained p value = 0,003<0.05. The summary of thisresearch was there is the correlation between Depressions with Social Interactions of the Elderly inthe village of Upper Tombasian, District of WestKawangkoan.Keywords : Depression, Social Interaction, ElderlyAbstrak: Proses menua merupakan proses sepanjang hidup yang tidak hanya dimulai dari suatuwaktu tertentu, tetapi dimulai sejak permulaan kehidupan. Peningkatan jumlah lanjut usia diikutidengan permasalahan kesehatan yang dihadapi karena proses degenetatif. Dikarenakan perubahanfisik maupun psikologis dari lansia banyak dari mereka mengalami depresi yang merupakan salahsatu penyakit mental paling banyak yang terjadi didunia. Interaksi sosial merupakan hubunngansaling mempengaruhi antara individu satu dengan yang lainnya sehingga dapat mempengaruhi,mengubah, atau memperbaiki prilaku individu yang lain atau sebaliknya. Tujuan Penelitianmengetahui Hubungan Depresi dengan Interaksi Sosial pada Lanjut Usia di Desa Tombasian AtasKecamatan Kawangkoan Barat. Desain Penelitian ini menggunakan cross sectional yaitu data yangmenyangkut variabel bebas atau resiko dan variabel terikat atau akibat akan dikumpulkan dalamwaktu yang bersamaan. Teknik pengambilan Sampel menggunakan teknik purposive samplingdengan jumlah sampel sebanyak 61 orang. Hasil uji statistic Chi-Square test dengan tingkatkepercayaan 95% (Î±=0,05) dan diperoleh p value 0,003 < 0,05. Simpulan yaitu terdapat HubunganDepresi dengan Interaksi Sosial pada Lanjut Usia di Desa Tombasian Atas Kecamatan KawangkoanBarat.Kata Kunci : Depresi, Interaksi Sosial, Lansia